AN ANALYSIS OF DEIXIS ON TEDX TALKS OF “STUDY SMARTER NOT HARDER” BY KIKI FAN - Fretty Ariani Putri Adi; Yulianto Sabat; Lailatul Musyarofah (PROJECT (Professional Journal of English Education), 2024)
The purpose of the research  is to assess the types of deixis and the prevailing deixis in the YouTube video of TEDx Talk. This article focuses on the researcher's explanation of the types of deixis and the primary deixis employed in the speech. This study is structured based on George Yule's hypothesis. According to Yule's theory, deixis may be categorized into three parts: person deixis, spatial deixis, and temporal deixis. This study employs a pragmatic approach, using a qualitative research methodology. The data in this study is derived from Kiki Fan's speech on TEDx talks, which has a duration of 8 minutes and 39 seconds. The data was examined using video transcripts and then identifying words that had deixis terms. This study demonstrates that Kiki used 3 types of deixis, including personal deixis, spatial deixis, and temporal deixis. This research  demonstrate that the form of deixis that is commonly used is person deixis. The researcher found 39 total of the deixis in the video. There are a 27 words that indicate a person deixis, 6 words that indicate spatial deixis, and 6 words that indicate temporal deixis.